Diseño de una metodología para la configuración genérica de una red de valor extendida, un estudio de caso centrado en la compañía focal (2018)
This paper documents and analyzes the operation of extended supply chains and the impact of local integrators on the management of distribution or marketing processes in different international regions. In this way the study is developed through the application of mixed methods of research, that is, it combines qualitative and quantitative methodologies, so that in the first stage, through secondary sources of information, a contextualization, characterization and definition of the key elements for the configuration of extended value networks. In order to ensure the convergence of these identified constructs, in the second stage a diagnosis is generated and its corresponding validation through the collection of information in primary sources. Based on these results, a proposal is generated for the configuration of this type of networks, in order to increase the insertion of Colombian companies in the extended systems.